Kerentanan DAS Cikeas ditinjau dari perspektif sosial ekonomi dan kelembagaan - Kunandar Prasetyo; Hefni Effendi; Gatot Prayoga; Andrian Rizaldy Azhar; Tri Permadi; Dewanti Pratiwi (Jurnal Pengelolaan Lingkungan Berkelanjutan (Journal of Environmental Sustainability Management), 2021)
The research aimed to determine the vulnerability level of the Cikeas watershed in terms of socio-economic and institutional aspects. The primary data collection method used purposive and snowball sampling. Secondary data were obtained from the Environmental Agency (DLH), Ciliwung Cisadane River Basin Center (BBWS) and Central Statistics Agency (BPS). Data analysis used quantitative descriptive analysis based on the formulation of watershed level characterization system. The vulnerability level of the Cikeas watershed in social aspects (population density and traditional values) was very high (very vulnerable). Conservation behaviour was classified as not vulnerable and somewhat vulnerable. On the economic aspect, most sub-districts in the Cikeas watershed were classified as somewhat vulnerable. The dominant economic sector was in the form of services. In terms of the institutional aspect, it was classified as not vulnerable and somewhat vulnerable because there were formal and informal institutions that have played an active role in the Cikeas watershed conservation activities. Watershed problems were related to the community's concern for environmental management. Thus, the involvement of the community and other relevant stakeholders in the planning, formulation, implementation of watershed policies was indispensable to achieve sustainable watershed management.